Effects of Covid-19 fear on the attitudes toward Covid-19 vaccination in reproductive women - (:unkn) unknown (My University, 2021)
This research aimed to determine the effect of Covid-19 fears on attitudes of women of reproductive age toward Covid-19 vaccination. This descriptive cross-sectional study was conducted with 413 women aged 18-49. "Participant Identification Form," "Fear of Covid-19 Scale (FCV-19S)" and "Attitudes Towards Covid-19 Vaccine Scale (ATV-Covid-19)" were used to collect data. Kruskall Wallis test, Man Whitney U test and Spearman correlation test were used to evaluate the data. The mean FCV-19S total score of the women within the scope of the study was 18.70 ± 5.34. The mean score of the positive attitude sub-dimension of ATV-Covid-19 of women was 14.09 ± 3.80, the mean score of the negative attitude sub-dimension was 16.21 ± 3.26. A positive, weak and statistically significant correlation was found between FCV-19S total score and ATV-Covid-19 positive attitude sub-dimension mean score (p < 0.05). It was determined that the women within the scope of the study had a moderate fear of Covid-19. However, more women had positive than negative attitudes toward Covid-19 vaccines. In addition, as the level of fear of Covid-19 increases, positive attitudes toward the Covid-19 vaccines increase.